Existence of solutions of integral equations with asymptotic conditions. (August 2018) - Cabada, Alberto; López-Somoza, Lucía; Tojo, F. Adrián F.
Abstract: In this work we will consider integral equations defined on the whole real line and look for solutions which satisfy some certain kind of asymptotic behavior. To do that, we will define a suitable Banach space which, to the best of our knowledge, has never been used before. In order to obtain fixed points of the integral operator, we will consider the fixed point index theory and apply it to this new Banach space.